A noção de perspectivismo na filosofia de Blaise Pascal - Pinto, Rodrigo Hayasi (2006)
The aim of this thesis is to understand Blaise Pascal's philosophical conception of science and morality on the basis of a more fundamental notion the notion of perspectivism. By not basing knowledge on ultimate and absolute terms, the French philosopher pointed the way to a new kind of knowledge, no longer guided by metaphysics, but by a hypotheticaldeductive ideal. This new kind of knowledge was to have provisional principles as points of departure, their rôle being that of epistemological perspectives in the sphere of science and practice.